Redes sociais digitais e a comunicação interna: manual de conduta como ferramenta estratégica para as organizações - Santos, Penélope da Silva Almeida [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This dissertation analyzes the scenario of social interactions mediated by Social Networks Digital in the organizational context, including organization, workforce and the use of digital social networks. The emphasis is on preparing the Manual of Conduct, specific to the use of these networks, such as internal communication strategy for organizations. The overall goals is to understand how to conduct manuals and business ethics, strategic tool for organizational communication with internal stakeholders are addressing issues related to the use of digital social networks. The methodology used are: 1) bibliographic research on Communication, Organizational Culture, Identify, Image and Organizational Reputation, Internal Communication, Social Media and Digital Communications Addressed; 2) exploratory research to survey and analysis of layoffs arising from the use considered inappropriate online social networks by the internal public, though news stories selected on the Internet; and 3) Manual content analysis and ethical conduct of three companies: the Brazilian Agricultural Research Corporation (Embrapa), the NovAmerica and Communications Agency Group machine. The main results are identified the need to establish a participatory process of the the workforce in the preparation of manuals of conduct for digital social networks; that textbooks should mirror the the organizational culture and especially should be used as a strategic tool of communication with the workforce

Esta dissertação analisa o cenário das interações sociais mediadas pelas redes sociais digitais no contexto organizacional, abrangendo organização, público interno e o uso das redes sociais digitais. A ênfase é dada na elaboração do Manual de Conduta, específico para o uso dessas redes, como estratégia de comunicação interna para as organizações. O objetivo geral é compreender como os manuais de conduta e ética empresarial, ferramenta estratégia de comunicação organizacional como o público interno, estão abordando questões relacionadas ao uso das redes sociais digitais. Como metodologias são utilizadas: 1) pesquisa bibliográfica sobre Comunicação, Cultura Organizacional, Identidade, Imagem e Reputação Organizacional, Comunicação Interna, Redes Sociais Digitais e Comunicação Dirigida; 2) pesquisa exploratória para levantamento e análise de demissões provenientes do uso considerado inadequado das redes sociais digitais por parte do público interno, por meio de matérias jornalísticas selecionadas na internet; e 3) análise de conteúdo do manual de conduta e ética de três empressas; a Empresa Brasileira de Pesquisa Agropecuária (Embrapa), a NovAmerica e a Agência de Comunicação Grupo Máquina. Como principais resultados, identificaram-se a necessidade de estabelecer um processo participativo do público interno na elaboração dos manuais de conduta para as redes sociais digitais; que os manuais devem espelhar a cultura organizacional e principalmente devem ser utilizados como ferramenta estratégica de comunicação com o público interno
Keywords: Comunicação; Cultura organizacional; Conduta - Manuais, guias, etc; Ética; Redes sociais on-line; Communication